2009
DOI: 10.1186/1471-2148-9-44
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of stress signalling pathways in fungi

Abstract: Background: Microbes must sense environmental stresses, transduce these signals and mount protective responses to survive in hostile environments. In this study we have tested the hypothesis that fungal stress signalling pathways have evolved rapidly in a niche-specific fashion that is independent of phylogeny. To test this hypothesis we have compared the conservation of stress signalling molecules in diverse fungal species with their stress resistance. These fungi, which include ascomycetes, basidiomycetes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(202 citation statements)
references
References 154 publications
12
189
0
1
Order By: Relevance
“…but many upstream sensors and downstream transcriptional regulators have diverged substantially 9 . On this basis one might have expected the heat shock response to have diverged in fungi that inhabit thermally buffered niches, such as the clinically important pathogen C. albicans 10 , which is obligately associated with warm-blooded animals 11 .…”
Section: Introductionmentioning
confidence: 99%
“…but many upstream sensors and downstream transcriptional regulators have diverged substantially 9 . On this basis one might have expected the heat shock response to have diverged in fungi that inhabit thermally buffered niches, such as the clinically important pathogen C. albicans 10 , which is obligately associated with warm-blooded animals 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies designed to elucidate the cellular mechanisms that trigger toxicity and cell death have been reported in this yeast system (Braun et al, 2009). In the current investigation, we chose C. albicans strain CC504 as a test organism since in previous studies strains of C. albicans appeared Manen et al 71 to be more resistance to oxidative stress induced by different chemicals tested and hyphal filaments were readily demonstrable under defined growth conditions (Chandra et al, 2001;Whiteway et al, 2007;Nikoloau et al, 2009;Jamieson et al, 1996). We have demonstrated in control experiments, that parental cells and the CC504-CMV derivative strain did not exhibit immunolabeling with anti-tau antibody, which suggests that C. albicans does not contain a protein with epitopes similar to the human tau protein.…”
Section: Discussionmentioning
confidence: 99%
“…While we have earlier commented on the evolutionary conservation of stress response elements, a comparative study of fungal stress responses by Nikolaou et al (2009) has revealed a more nuanced situation. When stress response pathways are compared across several fungal species, it is found that there is extensive, niche-specific divergence of sensory and response elements, whereas core components of pathways (especially multifunctional components) are phylogenetically conserved.…”
Section: Future Perspectivesmentioning
confidence: 99%